Analisis Minat Belajar Matematika Mahasiswa pada Mata Kuliah Teori Bilangan - Dwi Syaputri; Hasanuddin . (CV.ITTC INDONESIA, 2026)
This study aims to analyze students' learning interest in the Number Theory course. Number Theory contains abstract concepts and requires strong reasoning skills, so learning interest is an important factor in supporting students' success. This research used a quantitative descriptive approach. The respondents were Mathematics Education students who had taken Number Theory. Data were collected through a questionnaire distributed online using Google Form. The instrument measured four indicators of learning interest: enjoyment, interest, attention, and student involvement. The data were analyzed using percentage calculations and categorized based on predetermined criteria. The results showed that students' overall learning interest reached 82.1%, which belonged to the very high category. The enjoyment indicator obtained the highest score at 89.0%, followed by attention at 82.2%, involvement at 78.0%, and interest at 79.0%. These findings indicate that students have strong motivation, focus, and seriousness in understanding Number Theory, although practical application-based interest still needs to be strengthened.